Humanistic entrepreneurship and fear-free survival in times of health emergency in Ibero-America - Gamarra-Chávez, Carlos Antonio (2022)
Entrepreneurship that catalyzes opportunities and changing scenarios to develop new brand concepts and their value propositions, has emerged with great force in recent times as a result of the health emergency. In this sense, a humanistic trend has evolved that seeks to enhance the collaborative aspects of entrepreneurs and has remained in the hearts of users. We present data and cases from Ibero-America on these people, who, showing attitude and resilience, have focused on responding to users seeking satisfaction, good treatment, as well as being able to buy and satisfy their needs in a sensitive and empathic way. These actions have contributed to a survival without major fears, which are already caracteristic in the Iberoamerican región. We also suggest taking advantage of the passage through higher educational institutions to continue strengthening the entrepreneurial spirit and humanistic behaviors, which in times of crisis such as the one we have been experiencing recently, result in a competitive advantage to meet needs and requirements in a differentiated way. New social solutions, permanent and sensitive innovation, as well as the adequate predisposition, make us visible to others and constitute a positive style of facing scenarios of uncertainty and crisis. Humanist entrepreneurship in Ibero-America is still present, survives and walk safely into the future, strengthening its links with society.